Analisis Yuridis Penerapan Pasal 1320 KUHPerdata Terhadap Sistem Ijon pada Petani Cengkeh di Desa Kaidundu Sebagai Kearifan Lokal - Aid Pramudya Husain; Mutia Cherawaty Thalib; Dolot Alhasni Bakung (Jurnal Mahasiswa Kreatif, 2023)
The purpose of this study was to identify and analyze the application of Article 1320 of the Civil Code regarding the bonded bondage system to clove farmers as local wisdom in preventing the occurrence of problems that arise because of the clove bonded agreement and to find out the obstacles faced in the application of article 1320 of the civil code to the bonded system. On Clove Farmers in Kaidundu Village as Local Wisdom. Research Using this type of normative-empirical research. By using several approaches, namely: statutory approach (statue approach), case approach (case approach). The results of this study indicate that: First, the clove bonded bondage system in Kaidundu Village is a custom or habit that was born and developed in the Kaidundu Village community since the last decades, the agreement system by means of bonded bondage involves sellers (farmers) and buyers (middlemen). . However, based on the law in force in article 1320 it is stated that, that the legal requirements for an agreement are agreement, competence, a certain matter and a lawful cause. However, in reality in society not all parties understand and understand what an agreement is considered. So that researchers can conclude that the bondage system in Kaidundu Village is a habit that has been passed down from generation to generation, but the community must understand and know that there are rules governing this bondage system. Second, the obstacles faced by the people of Kaidundu Village, especially those involved in the case of the Clove ijon system, several obstacle factors faced, namely: Legal factors, where there is no agreement or agreement that binds both parties, both the seller (farmer) and buyer (middleman). And there are no regulations in the form of Perdes (Village Regulations) which regulate the existence of the clove bondage system. The ijon system agreement is only based on trust.